2016
DOI: 10.1137/15m1052743
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Representation of Parameter Space for Switching Networks

Abstract: We describe the theoretical and computational framework for the Dynamic Signatures for Genetic Regulatory Network ( ) database. The motivation stems from urgent need to understand the global dynamics of biologically relevant signal transduction/gene regulatory networks that have at least 5 to 10 nodes, involve multiple interactions, and decades of parameters. The input to the database computations is a regulatory network, i.e. a directed graph with edges indicating up or down regulation. A computational model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
158
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(158 citation statements)
references
References 44 publications
0
158
0
Order By: Relevance
“…By Definition 1.1, the restrictions x| A and x| B onto A = x −1 (ξ) and B = x −1 (ξ ) are again trajectories. By Definition 4.4, x| A and x| B are solutions to Equation (4). Such solutions are monotonic, so it follows that x| A and x| B are increasing.…”
Section: Dsgrn Model For Regulatory Networkmentioning
confidence: 99%
“…By Definition 1.1, the restrictions x| A and x| B onto A = x −1 (ξ) and B = x −1 (ξ ) are again trajectories. By Definition 4.4, x| A and x| B are solutions to Equation (4). Such solutions are monotonic, so it follows that x| A and x| B are increasing.…”
Section: Dsgrn Model For Regulatory Networkmentioning
confidence: 99%
“…We have introduced a construction and counting problem important to the dynamical classification of switching systems across global parameter space [5]. We have shown that the parameterization of a switching system gives rise to a natural partial order that is subject to algebraic constraints.…”
Section: Resultsmentioning
confidence: 99%
“…Typically, a regulatory network is represented as an annotated directed graph, where each vertex represents the concentration of a molecular species (e.g. protein, mRNA), and an edge from node i to node j indicates that i directly regulates j, as in [5]. Definition 2.1.…”
Section: Switching Systemsmentioning
confidence: 99%
See 2 more Smart Citations